Higher education, emerging technologies, and community partnerships : concepts, models and practices - Carpenter, Russell G., 1979-; Bowdon, Melody A., 1967- (Hershey PA : Information Science Reference, 2011)
"This book is a comprehensive collection of research with an emphasis on emerging technologies, community value, and corporate partnerships, providing strategies to implement partnerships"--Provided by publisher.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Education, Higher -- Effect of technological innovations on; Distance education -- Computer-assisted instruction; Educational technology; Community education -- United States